El presente histórico en la guerra del Golfo - Martinic, Zvonimir (Revista de Estudios Árabes, 2014)
The author describes the decline and end of the Soviet era, that allowed the instauration of a new world order dictated by the U.S.A. When Iraq invaded Kuwait in 1990, it disrupted American plans for that region. The First Gulf War ensued and resulted in the defeat of the invader, thus allowing wider American hegemony world wide.